REFORMING THE SIMPLIFIED TAXATION SYSTEM UNDER THE CONDITIONS OF THE MARITAL STATE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The simplified system of taxation in Ukraine is implemented as a special temporary tax regime to stimulate the detinization of small and medium-sized businesses by reducing the tax burden and using a simpler mechanism of taxation, accounting and reporting. The simplified taxation system has undergone significant changes during its existence, due to the need to take into account the current economic situation and budget needs. During the war, the government, in order to support business, significantly changed the simplified taxation system, expanding preferential tax conditions.The purpose of the research is to analyze the features of the simplified taxation system in Ukraine during the war, to study the main problems of the modern simplified taxation system and to develop the main directions of its improvement.The article systematizes the main benefits for business in the system of simplified taxation and reveals the main shortcomings of its functioning. A comparative description of small business taxation in Ukraine and European countries has been carried out. The necessity of reforming the simplified taxation system has been proposed and ways have been proposed.In general, the simplified taxation system in Ukraine continues to be an important tax regime for small and medium-sized enterprises. Recent changes in the system were aimed at providing support to business in general, as tax benefits were not only for small businesses, but also for large ones. While supporting the need to return to pre-war taxation, we also consider it necessary to increase the rates of the single tax for entrepreneurs of I-II groups, establish the dependence of rates not on the living wage and the minimum wage, but on the volume of income, strengthen control over compliance with tax legislation and combat tax evasion taxes.
Keywords: single tax, simplified taxation system, tax benefits, small business, martial law.